Analisis Rasio Aktivitas Untuk Mengukur Kinerja Keuangan dalam Mengambil Keputusan Investasi pada PT. Indofood Sukses Makmur Tbk Periode 2021-2023 - Suriana Agustina Putri; Anis Safia; Reny Amandha; Joni Hendra K (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
Financial performance analysis can be seen from several financial ratios, one of which is the activity ratio. The purpose of this study was to determine the effect of activity ratios on investment decisions. The research method used is quantitative research method with secondary data. This research was conducted at PT Indofood Sukses Makmur Tbk which is listed on the Bursa Efek Indonesia  for the period 2021 - 2023. The results of the study indicate that PT. Indofood Sukses Makmur Tbk needs to improve its operational efficiency, especially in managing inventory, receivables, and assets because the results of the study prove that the company's industry standards do not reach their targets in this study. Although the company has shown improvement in the management of receivables, there is still an opportunity to improve efficiency in the use of assets and inventory. By improving operational efficiency, the company can increase investment attractiveness and achieve better performance.